Anthropological approaches to the relationship between aesthetics and ethics. Issue 2 (3rd July 2017) - Crăciun, Magdalena
Abstract : The relationship between aesthetics and ethics has long been a topic of scholarly debate. However, in anthropology this relationship has been less consistently problematised. In addition, the very terms of the relationship have occupied rather peculiar positions on the anthropological agenda, the aesthetic experiences and artistic practices of people around the world being an established topic of concern, while mundane ethical reflections and actions have only recently become a topic of sustained investigation. This special issue is explicitly concerned with this relationship, its major achievement being to demonstrate what it means to capture ethnographically how, when and why the aesthetic and the ethical intersect, overlap or become opposed. This introduction examines milestones in the consideration of aesthetics and, respectively, ethics in anthropology. Rather than providing an intellectual history, its main aim is to locate the issue's contributions in relation to past and current anthropological debates.